The Effectiveness of YouTube as an E-Resource on Students’ Writing Learning - Euis Meinawati; Prapti Wigati Purwaningrum; Sufi Alawiyah; Herlin Widasiwi Setianingrum (STAI Hubbulwathan Duri, 2022)
The purpose of this research was to find out the effectiveness of YouTube as an electronic learning resource in English writing learning. An exploratory mixed method was used in this study. Research instruments included tests, observations and questionnaires. The participants in this study were all third-semester English majors at Bina Sarana Informatika University in Jakarta. The participants were 100 students that were taken randomly. The researcher collected the data from September until December 2021. The result of the English essay writing test was analyzed by using a t-test. The observation was be done during the learning process and the questionnaire used to get students' input about the effectiveness of YouTube as an e-resource. The results of the study concluded that YouTube as an e-resource has a positive impact on the ability to write English essays. The test results before and after implementing YouTube as an e-resource were t-stat (8.76) t-table (2.022), which means Ho was rejected and H1 was accepted. While the Pearson correlation was 0.732. Students also gave a positive view of the use of YouTube during essay writing activities. This can be seen in the average value which was dominated by strongly agreed answers. This study concluded that learning resources for writing should be presented as learning resources that involve audio-visual and interesting so that story ideas can be developed.